The Immunomodulatory Signature of Extracellular Vesicles From Cardiosphere-Derived Cells: A Proteomic and miRNA Profiling - López, Esther; Marinaro, Federica; de Pedro, María de los Ángeles; Sánchez-Margallo, Francisco Miguel; Gómez-Serrano, María; Ponath, Viviane; Pogge von Strandmann, Elke; Jorge, Inmaculada; Vázquez, Jesús; Fernández-Pereira, Luis Miguel; Crisóstomo, Verónica; Álvarez, Verónica; et al. (Frontiers in Cell and Developmental Biology, 2020)
Experimental data demonstrated that the regenerative potential and immunomodulatory capacity of Cardiosphere-Derived Cells (CDCs) is mediated by paracrine mechanisms. In this process, extracellular vesicles derived from CDCs (EV-CDCs) are key mediators of their therapeutic effect. Considering the future applicability of these vesicles in human diseases, an accurate preclinical-to-clinical translation is needed, as well as an exhaustive molecular characterization of animal-derived therapeutic products. Based on that, the main goal of this study was to perform a comprehensive characterization of proteins and miRNAs in extracellular vesicles from porcine CDCs as a clinically relevant animal model. The analysis was performed by identification and quantification of proteins and miRNA expression profiles. Our results revealed the presence of clusters of immune-related and cardiac-related molecular biomarkers in EV-CDCs. Additionally, considering that priming stem cells with inflammatory stimuli may increase the therapeutic potential of released vesicles, here we studied the dynamic changes that occur in the extracellular vesicles from IFNγ-primed CDCs. These analyses detected statistically significant changes in several miRNAs and proteins. Notably, the increase of Interleukin 6 (IL6) protein, as well as the increase of mir-125b (that targets IL6 Receptor) was especially relevant. These results suggest a potential involvement of EV-CDCs in the regulation of the IL6/IL6R axis, with implications in inflammatory-mediated diseases.